2017
DOI: 10.1016/j.actpsy.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Attentional interference is modulated by salience not sentience

Abstract: Spatial cueing of attention occurs when attention is oriented by the onset of a stimulus or by other information that creates a bias towards a particular location. The presence of a cue that orients attention can also interfere with participants' reporting of what they see. It has been suggested that this type of interference is stronger in the presence of socially-relevant cues, such as human faces or avatars, and is therefore indicative of a specialised role for perspective calculation within the social doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 27 publications
1
38
1
1
Order By: Relevance
“…These findings, supporting the Perspective-Taking theory, run counter to the "Perceptual" theory, which argues that the perceptual features (i.e., the direction of other's face/nose/posture) are sufficient to explain attentional orientation [14][15][16]. These studies found that human avatars spontaneously orient attention of the observers even when the human avatars cannot see the stimuli either because a physical barrier prevents the view, as in Cole et al [14] or when the cue employed in the dot perspective task does not have a mental state (e.g., an arrow, or a camera) as in Wilson et al [16]. According to this theory, the effects showed in the dot perspective task are due to domain-general processes rather than perspective taking.…”
Section: Introductionmentioning
confidence: 55%
“…These findings, supporting the Perspective-Taking theory, run counter to the "Perceptual" theory, which argues that the perceptual features (i.e., the direction of other's face/nose/posture) are sufficient to explain attentional orientation [14][15][16]. These studies found that human avatars spontaneously orient attention of the observers even when the human avatars cannot see the stimuli either because a physical barrier prevents the view, as in Cole et al [14] or when the cue employed in the dot perspective task does not have a mental state (e.g., an arrow, or a camera) as in Wilson et al [16]. According to this theory, the effects showed in the dot perspective task are due to domain-general processes rather than perspective taking.…”
Section: Introductionmentioning
confidence: 55%
“…The claim that allocentric information is available to perception is controversial (e.g., Wilson et al 2017). What is novel in this study is that we are focusing on allocentric information for reasoning rather than perception.…”
mentioning
confidence: 90%
“…This phenomenon produces the opposite of an egocentric bias: an allocentric bias. However, some recent papers have offered an alternative perceptual interpretation of 4 the phenomenon (Cole et al, 2015;Santiesteban et al, 2014;Wilson et al 2017). According to this perceptual interpretation, people are not directly affected by the others' perspective but rather by basic perceptual directional characteristics of the stimuli.…”
Section: Egocentric and Allocentric Biasesmentioning
confidence: 99%
See 2 more Smart Citations